IL-6/GATA2/SERPINE1 pathway is implicated in regulating cellular senescence after acute kidney injury - Su, Hongshuang; Lin, Xiaoxi; Paredong, Ayinuer; Yao, Congcong; Zhang, Yan; Geng, Mengke; Guan, Yuqian; Gong, Lichao; Jiang, Feng; Lv, Qi; Shou, Songtao; Jin, Heng (Frontiers in Molecular Biosciences, 2025)
PurposeAcute kidney injury (AKI) secondary to Rhabdomyolysis syndrome represents a life-threatening complication, characterized by notably high incidence and mortality rates. The role of cellular senescence in the progression of AKI has increasingly garnered attention in recent years. Our previous research has demonstrated that remote ischemic postconditioning (RIPC) can attenuate renal cellular senescence and elevation of serum level of interleukin-6 (IL-6) induced by ischemia-reperfusion injury following crush injury. The objective of this study is to investigate the specific role of IL-6 in Rhabdomyolysis-induced AKI (RM-AKI).MethodsWe established a mouse model of RM-AKI by intramuscular injection of glycerol and simulated RM-AKI at the cellular level by treating Hk-2 cells with myoglobin. Tocilizumab (TCZ), a humanized monoclonal antibody against the interleukin-6 (IL-6) receptor, is a key substance. IL-6, a multifunctional cytokine, plays a crucial role in the occurrence and development of various kidney diseases. It can promote inflammatory responses, cell proliferation, fibrosis, and other processes. TCZ exerts a protective effect on the kidneys by specifically binding to the IL-6 receptor and blocking the signal transduction of IL-6. Additionally, the levels of IL-6 were detected by employing ELISA kits. RNA sequencing analysis was performed on cells treated with myoglobin and tocilizumab. Flow cytometry was utilized to assess cell cycle distribution and the percentage of senescent cells. The expression levels of SERPINE1, GATA2, p53, and p21 were determined by real-time quantitative PCR and Western blot. Additionally, a dual-luciferase reporter gene assay was conducted to validate the binding effect of SERPINE1 and GATA2.ResultsTranscriptome Analysis revealed that genes including GATA2 and SERPINE1 were downregulated in HK-2 cells following tocilizumab treatment. Inhibition of the IL-6 receptor by tocilizumab in these cells led to a reduction in cellular senescence, accompanied by decreased of the cell cycle regulatory proteins P53 and P21 in mRNA and protein levels, while alleviating cell cycle arrest. Additionally, a dual-luciferase reporter assay confirmed that GATA2 binds to the promoter of SERPINE1 (PAI-1), thereby initiating its transcription.ConclusionThe IL-6/GATA2/SERPINE1 pathway mediates cellular senescence after acute kidney injury, and inhibiting IL-6 can alleviate AKI-induced cellular senescence, providing an important basis for exploring new therapeutic strategies.